Ibsen in Georgia: milestones in the reception - Loria, Kakhaber (Nordlit, 2015)
From early on, Henrik Ibsen has played an important part on the Georgian stage, as well as in Georgian literary thought. Since the publication of Ibsen’s biography in the newspaper Kvali in 1897, the dramatist has been continuously discussed, translated, written about and performed in Georgia. Ibsen has been received under different circumstances and by different generations: to pursue the reception of Ibsen in Georgia is, in a way, to pursue the development of Georgian intellectual and cultural history in the period. In Georgia, various celebrations of Ibsen’s birth and death were marked, in a number of articles, and even a little book on Ibsen by Akaki Gelovani were published. Well-known Georgian authors have also been interested in Ibsen. In our context, one should mention that both Mikhail Javakhishvili and Konstantin Gamsakhurdia, the classic authors of modern Georgian prose, wrote famous essays on Ibsen. Ibsen was and is constantly referred to in Georgian literary studies, not least in connection with Georgian writers. In post-Soviet Georgia, Ibsen is very much on the agenda, and his plays are produced and discussed as they always have been.